Design of Single-Stage Flyback PFC Converter for LED Driver - Wang Qi; Wu Jie; Baohua Lang (Universitas Ahmad Dahlan, 2016)
A light emitting diode (LED) driver based on single-stage power factor correction (PFC) is presented in this paper. The designed LED driver using flyback topology can achieve power factor correction and constant-current drive LED in boundary conduction mode. The circuit principle is described in detail, the formulas for MOS switch-on time, switching frequency and the main impact factor of power factor are proposed. The experiment results show that the designed LED driver has high power factor, stable output and it can drive the LED with high efficiency.